Heterotopias in novels by Sydney Owenson, Jane Austen, Mary Shelley, and Charlotte Brontë - Yi, Jingxuan (2023)
In this thesis, I explore seven novels written by Sydney Owenson, Jane Austen, Mary Shelley, and Charlotte Brontë, all major women writers of the early nineteenth century. I will argue that these women writers, often financially dependent on their pens, strategically created literary characters whose embodied experiences of time, space and motion seek to redefine and reconstruct their relationships with social spaces. I approach the spatial in their works by using Foucault’s concept of heterotopia as a critical framework. Heterotopias are Other spaces, off-center in comparison with normal or everyday spaces, possessing manifold meanings. I aim to trace how heterotopias function in different cultural and historical contexts, arguing that heterotopias have the potential to transcend binary power structures and provide a space for otherness, although they fail to overthrow the dominant social order. I will also focus on frame narratives and the liminal space of annotation, following Foucault’s notion of textual heterotopias that ‘destroy “syntax” in advance’, something that allows ‘words and things (next to and also opposite one another) to “hold together”’.1 Ultimately, my thesis argues that the spatial is an important critical category to understand these women writers’ engagement with a complex mesh of political, cultural and historical concerns. This thesis aims to provide a fresh perspective on the deictic functions of heterotopias in my chosen works. The introduction offers an outline of my theoretical approach, and a discussion of the concept of heterotopia, from its etymology to its literal and metaphorical usage. My main analysis comprises four chapters. Chapter One focuses on cross-cultural contact zones in Owenson’s The Wild Irish Girl (1806) and The Missionary (1811), where the liminal, often shifting identities of the Oriental Other pose a challenge to the assumptions of colonial authority. Following Edward Said and Homi K. Bhabha, I explore the concept of hybridity as an interstitial space to deconstruct oppositional discourses of dominance and resistance. The acts and artifice of storytelling form the focus of the second chapter, in which I argue that Shelley’s use of frame narratives in Frankenstein (1818) and The Last Man (1826) reveals a non-linear understanding of history that contests Enlightenment ideas of progress and causation. Working with Foucault’s fourth principle of heterotopias which emphasizes co-existence of diverse times in the same place, I argue that heterotopias arise as a hybrid effect of fiction and reality. Women’s protean subject positions under benevolent patriarchy in Pride and Prejudice (1813) and Mansfield Park (1814) are the focus of the third chapter. I examine how a heterotopic experience can promote female agency and destabilize binary gender relations, even while women are still restrained by patriarchal controls. In the fourth chapter, I turn to the private, inner world of the female character Lucy Snowe in Villette (1853), arguing that this is a heterotopia that facilitates the formation of a multifaceted self. The conflicted subject position occupied by Lucy reflects her difficult struggle to transcend gender and class boundaries. The Conclusion draws together my findings and argues that the analysis of these physical, psychic and textual spaces through the lens of heterotopias opens up the possibility for imagining a new embodied subaltern subjectivity.